Pengembangan Media Model Mock-Up Lengan Puff Pada Elemen Pembuatan Blus Di Fase F SMKN 1 Sarirejo Lamongan - Aura Najwa Bilqis; Peppy Mayasari (CV. SINAR HOWUHOWU, 2026)
This study aims to describe (1) the level of feasibility of the puff sleeve mock-up model media for blouse making elements in phase F of SMKN 1 Sarirejo Lamongan. (2) student learning outcomes after using the puff sleeve mock-up model media for blouse making elements in phase F of SMKN 1 Sarirejo Lamongan. (3) student responses to the puff sleeve mock-up model media for blouse making elements in phase F of SMKN 1 Sarirejo Lamongan. The study is included in development research, known as R&D, using the ADDIE model approach. The study was conducted on April 28, 2026, at SMKN 1 Sarirejo Lamongan with 15 Phase F students on the sleeve making element. Data collection techniques used material validation research, media validation, student product assessment, and student response questionnaires. The research instruments used were (1) a media validation sheet to assess the feasibility of the mock-up model media, (2) a product assessment sheet using the developed puff sleeve mock-up model, and (3) a student response questionnaire to measure students' understanding of the model and to assess their understanding. The data analysis technique used a descriptive approach, using the average validation results of the material and media, the value of student practice results based on the minimum KKTP requirements, and calculating the average of the student questionnaires. The results of the study stated: (1) the feasibility of the validation results by three validators with an average of 4.28, which means the model media is very suitable for use in learning, (2) Student learning outcomes in making the puff sleeve mock-up model in phase F of SMKN 1 Sarirejo Lamongan were 15 students declared complete, (3) Student responses to the use of the model media showed a very high level of acceptance with an average presentation of 4.9.